Optimization of Microwave-Assisted Extraction of Flavonoids and Antioxidants from Vernonia Amygdalina Leaf using Response Surface Methodology - Alara, Oluwaseun Ruth; Nour, A. H.; Olalere, Olusegun Abayomi (Elsevier Ltd, 2018)
In this study, the microwave-assisted extraction (MAE) variables were optimized using a face-centered central composite design of response surface methodology for optimal recoveries of total flavonoid content (TFC) and antioxidant capacities (DPPH and ABTS) of Vernonia amygdalina leaf extract. The independent variables were irradiation time (5–15 min), microwave power level (400–600 W), temperature (90–110 °C), and feed-to-solvent ratio (0.08–0.13 g/ml). The ANOVA results showed that TFC, DPPH and ABTS radical scavenging activities were significantly (p < 0.0001) affected by irradiation time, microwave power level and feed-to-solvent ratio, indicating a good agreement between the experimental and predicted values. The optimal conditions for maximum recoveries of TFC (87.05 ± 1.03 mg QE/g d.w. (n = 3)) and antioxidant capacities (DPPH scavenging of 94.05 ± 1.03% (n = 3), and ABTS scavenging of 95.93 ± 0.99% (n = 3)) were 7 min of irradiation time, 416 W of microwave power level, 100 °C of temperature, and 0.10 g/ml of feed-to-solvent ratio. More so, the optimized extract from MAE was compared with that of Soxhlet extraction technique, the extract from MAE possesses a high capacity of inhibiting antioxidants. Likewise, more chemical components from the GC–MS analysis were identified for the extract from MAE.